2nd. International Workshop on Additive Manufacturing and Sustainability (IWAM): book of abstracts - Rocha, João (Ed.) (2024)
We are pleased to present the International Workshop on Additive Manufacturing and Sustainability Book of Abstracts. This compilation brings together researchers, professors, and innovators from around the world who are advancing additive manufacturing (AM) and sustainable practices. As the global community prioritizes environmental responsibility, additive manufacturing has emerged as a transformative technology capable of revolutionizing industries while reducing ecological footprints. This workshop unites advanced research, innovative applications, and progressive strategies to examine how additive manufacturing can enhance sustainability. Within these pages, you will find a diverse array of abstracts showcasing ground-breaking work in areas such as: Sustainable materials and processes in AM, Energy efficiency and waste reduction, Circular economy and lifecycle analysis, Each contribution reflects a commitment to addressing the challenges and opportunities at the intersection of technology and sustainability. We hope this collection not only informs but also inspires collaboration and innovation among participants. We are profoundly grateful to the authors, reviewers, and organizers whose unwavering commitment has enabled the publication of this book. A special thank you to our sponsors and partners for their unwavering support in bringing this workshop to life. We appreciate your participation in this wonderful adventure. Let's work together to advance sustainability and innovation!